Análise em dimensão infinita: resultados essenciais - Oliveira, Gislaine Gonçalves de (2023)
In this work we present basic concepts necessary for the introductory study of Analysis in Infinite Dimensions. To this end, we will start by presenting some topics on metric spaces and topological spaces. Next, we will carry out a study in Functional Analysis, where the basic theory of continuous linear operators between normed spaces and Banach spaces will be presented, such as the classic Banach-Steinhaus, Open Mapping, Closed Graph and Hahn Banach theorems.